Enzymes and microorganisms jointly promote the fermentation of rapeseed cake - Song, Yujie; Sun, Litao; Zhang, Shuning; Fan, Kai; Wang, Huan; Shi, Yujie; Shen, Yaozong; Wang, Wenmei; Zhang, Jie; Han, Xiao; Mao, Yilin; Wang, Yu; et al. (Frontiers in Nutrition, 2022)
Rapeseed cake is a by-product of rapeseed oil separation. The nutritional components of rapeseed cake mainly include a variety of carbohydrates, proteins and minerals. In order to improve the conversion rate of rapeseed cake, we studied the physicochemical properties, the structure of microbial communities and the composition of metabolites of rapeseed cake after enzymatic fermentation. The results showed that the addition of enzymatic preparation increases the microbial diversity. The relative abundance of Bacillus, Lysinibacillus, Empedobacter, Debaryomyces, Hyphophora and Komagataella in enzymatic fermentation were significantly higher than that in natural fermentation. Unlike natural fermentation, microbial diversity during enzyme fermentation is specific, which improves fermentation efficiency. Otherwise, enzymatic fermentation promotes the conversion of macromolecular substances of rapeseed cake, which increases more small metabolites, such as fatty acids, organic acids, amino acids and their derivatives. The metabolite enrichment pathway mostly concentrated in sugar metabolism and fatty acid metabolism. In conclusion, after adding enzymatic preparation, enzymes and microorganisms jointly promote the transformation of macromolecules in the fermentation of rapeseed cake, which laid a good foundation for further utilization of rapeseed cake.